Volume 1: 32nd Design Automation Conference, Parts a and B 2006
DOI: 10.1115/detc2006-99545
|View full text |Cite
|
Sign up to set email alerts
|

Automating Redesign of Sheet-Metal Parts in Automotive Industry Using KBE and CBR

Abstract: Automating redesign is an approach for engineering designers to prevent design related manufacturability problems in early product development and thus reduce costly design iterations. A vast amount of work exists, with most research findings seemingly staying within the research community rather than finding its way into use in industrial settings where research issues have often evolved from the concerned applied research. The aim of this paper is to present an approach with industrial implementation potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Agarwal and colleagues (Agarwal & Cagan, 1998; Agarwal et al, 1999) have associated the shape grammar technique with parametric cost and applied it to the design of coffee makers (see Cagan, 2001, for a review on the use of shape grammars in engineering design). Numerous efforts have also been made to take into account the engineering and production constraints early in the development process, using knowledge-based engineering systems (see El-Sayed & Chassapis, 2005; Sandberg & Larsson, 2006; Lin et al, 2009; Johansson, 2011) or a combination of knowledge-based engineering and optimization systems, as in Petersson et al (2012), where the lightweight gripper constraint satisfaction and optimization system is based on the weighted sum technique. These works, even if they present interesting design systems, are not primarily concerned with diversity and choice.…”
Section: Gdss and Chtsmentioning
confidence: 99%
“…Agarwal and colleagues (Agarwal & Cagan, 1998; Agarwal et al, 1999) have associated the shape grammar technique with parametric cost and applied it to the design of coffee makers (see Cagan, 2001, for a review on the use of shape grammars in engineering design). Numerous efforts have also been made to take into account the engineering and production constraints early in the development process, using knowledge-based engineering systems (see El-Sayed & Chassapis, 2005; Sandberg & Larsson, 2006; Lin et al, 2009; Johansson, 2011) or a combination of knowledge-based engineering and optimization systems, as in Petersson et al (2012), where the lightweight gripper constraint satisfaction and optimization system is based on the weighted sum technique. These works, even if they present interesting design systems, are not primarily concerned with diversity and choice.…”
Section: Gdss and Chtsmentioning
confidence: 99%
“…Besides product and production platforms, Dadfar et al (2013) present a definition for technology platforms, which takes an integrated perspective of 'capabilities, physical aspects and know-how' as enablers of delivering product variety. Finally, both explicit (Lager 2017) and implicit (Sandberg and Larsson 2006;Karayel and Ozkan 2006;Xie et al 2001) descriptions of knowledge platforms were identified, all to support new product development process by reusing design knowledge. In summary, regardless of the type of platform or the origin of the definition, platforms are considered as means of facilitating high product variety for manufacturers in the process industry.…”
Section: Platformsmentioning
confidence: 99%
“…Integration of organisational functions has been addressed by multiple authors. Most of the papers identified in this cluster are related to sheet metal processing(Sandberg and Larsson 2006;Karayel and Ozkan 2006;Xie et al 2001;Chin and Tang 2002), and seek to decrease product development time by better integrating knowledge of product engineers and manufacturing engineers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar plans are retrieved using nearest neighbour search. Sandberg and Larsson [21] use KBE and CBR in an iterative process for automated design of sheet-metal parts. Both techniques are applied for part design, evaluation and optimization.…”
Section: Literature Reviewmentioning
confidence: 99%